Pengaruh Kualitas Konten, Konsistensi Unggahan, dan Engagement Terhadap Keberhasilan Pemasaran Afiliasi Shopee Pemula pada Media Sosial di Kabupaten Jombang - Khoiriyah, Nofita (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of content quality, posting consistency, and engagement on the success of novice Shopee affiliate marketing on social media in Jombang Regency, both partially and simultaneously. This study employed a quantitative approach using primary data collected through questionnaires. The research sample consisted of 100 respondents selected using a purposive sampling technique based on predetermined criteria. The data were analyzed using multiple linear regression analysis, while the hypotheses were tested using t-tests and an F-test. The results indicate that content quality has a positive and significant effect on the success of novice Shopee affiliate marketing, with a significance value of 0.004. Posting consistency has a positive and significant effect, with a significance value of 0.014, while engagement also has a positive and significant effect, with a significance value of 0.000. Simultaneously, content quality, posting consistency, and engagement have a significant effect on the success of novice Shopee affiliate marketing, with an F-value of 65.373 and a significance value of 0.000. The R Square value of 0.671 indicates that the three independent variables explain 67.1% of the variation in the success of novice Shopee affiliate marketing, while the remaining 32.9% is explained by other factors outside the research model.